Isolation and optimisation of culture conditions for a marine bioflocculant-producing bacterium and application of its bioflocculant in wastewater treatment - Selepe, Tlou Nelson; Maliehe, Tsolanku Sidney; Moganedi, Kgabo; Masoko, Peter; Mlaudzi, Vusimuzi (International Journal of Environmental Research and Public Health, 2022)
The application of bioflocculants has become an alternative to that of chemical flocculants in wastewater treatment due to their environmental friendliness and non-toxic effects. This study aimed at isolating a bioflocculant-producing bacterium from marine water, optimisation of its culture conditions, and investigation of the removal efficiency of its bioflocculant on pollutants in wastewater. The bacterium was identified by 16S rRNA gene analysis. Optimal carbon and nitrogen sources, inoculum size, temperature, pH, and time were determined by the one-factor-at-a-time assay. The cytotoxicity of the bioflocculant was assessed on African green monkey kidney and bovine dermis cells using a tetrazolium-based columetric (MTT) method. Its removal efficiencies on chemical oxygen demand (COD), biological oxygen demand (BOD) and sulphur were determined using the Jar test method. The bacterial isolate was identified as Ochrobactrum oryzae AB84113. A maximum flocculating activity of 92% and a yield of 3.768 g/L were obtained when a 1% (v/v) inoculum size was used in the presence of starch and yeast extract at pH 7, 30 ◦C, and after 72 h of cultivation. The bioflocculant demonstrated non-cytotoxic effects on bovine dermis and African green monkey kidney cells. The bioflocculant removed 98% COD, 91% BOD and 86% of Sulphur. The bioflocculant has potential for pollutant removal from industrial wastewater.
Journal article published in International Journal of Environment Research. Public Health 2022, 19, 10237
Keywords: Ochrobactrum oryzae AB84113; Bioflocculant; Flocculating activity; Removal efficient; Flocculants; Land treatment wastewater; Sewage -- Purification -- Electrochemical treatment